2023
DOI: 10.3390/antibiotics12010166
|View full text |Cite
|
Sign up to set email alerts
|

First and Second-Line Anti-Tuberculosis Drug-Resistance Patterns in Pulmonary Tuberculosis Patients in Zambia

Abstract: Background: Drug-resistant tuberculosis has continued to be a serious global health threat defined by complexity as well as higher morbidity and mortality wherever it occurs, Zambia included. However, the paucity of information on drug-susceptibility patterns of both first-line and second-line anti-tuberculosis (anti-TB) drugs, including the new and repurposed drugs used in the management of drug-resistant tuberculosis in Zambia, was the major thrust for conducting this study. Methods: A total of 132 bacteriol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
4
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 76 publications
2
13
4
3
Order By: Relevance
“…Compared to our finding, a higher rate of resistance of M. tuberculosis strains to at least one firstline anti-TB drug among new cases was reported by Yimer SA et al, (30.1%, 2012) [40] in Ethiopia; Mende N et al, (23.5%, 2023) [41] in Zambia; Thapa G et al, (31.1%, 2016) [42] in Nepal; Li Y et al, (34.1%, 2016) [43] in China;…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Compared to our finding, a higher rate of resistance of M. tuberculosis strains to at least one firstline anti-TB drug among new cases was reported by Yimer SA et al, (30.1%, 2012) [40] in Ethiopia; Mende N et al, (23.5%, 2023) [41] in Zambia; Thapa G et al, (31.1%, 2016) [42] in Nepal; Li Y et al, (34.1%, 2016) [43] in China;…”
Section: Discussioncontrasting
confidence: 88%
“…The rate of MDR-TB identified in this study was 5.8%, (9/156) among new presumptive TB cases and this was congruent to the rate of MDR-TB reported in the previous studies by Tessema B et al, (3.7%, 2012) [28], Yigzaw WB et al, (5.0%, 2021) [40] in Ethiopia; Yonge SA et al, (4.8%, 2017) [46] in Kenya and Dosso M et al, (5.3%, 1999) [32] in Côte d'Ivoire. However, compared to our study findings, a higher rate of MDR-TB was reported in the previous studies by Welekidan LN et al, (11.6%, 2020) [49], and Dagne B et al, (61.9%, 2021) [39] in Ethiopia; Ullah I et al, (9.3%, 2016) [35] in Pakistan; Monde N et al, (9.8%, 2023) [41] in Zambia, Thapa G et al, (15.6%, 2016) [42] in Nepal, Li Y et al, (13.2%, 2016) [43], and Zhou L et al, (18.8%, 2022) [50] in China and Aung WW et al, (18.3%,2015) [51], and Lobie TA et al, (2.3%, 2020) [30] in Ethiopia; Glasauer S et al, (3.3%, 2019) [34] in Germany. Notwithstanding this observation, the WHO estimate of 1.1% of MDR-TB in new TB cases revealed in the 2022 global tuberculosis report is much lower than the findings demonstrated in this study [15].…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…9 Other contributing factors to drug resistance include patient non-compliance, emerging mutations, and limited access to diagnosis and treatment. 9 Multi-drug-resistant (MDR) and extensively drug-resistant (XDR) TB strains pose significant treatment challenges, hindering effective care. 10 The emergence of drug-resistant TB, including strains resistant to rifampicin and multiple drugs, poses a significant danger to public health.…”
Section: Introductionmentioning
confidence: 99%